(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The paper examines approaches to low-emission spatial planning for small industrial towns in the Republic of Tatarstan, using Mendeleevsk and Zainsk as comparative case studies. The relevance of the study is determined by the fact that, under the transition to low-carbon development, the environmental burden in small towns is distributed unevenly and is shaped by sectoral specialization, the structure of stationary and mobile emission sources, energy infrastructure, and the spatial relationship between industrial zones and residential areas. The empirical basis of the study includes strategic and spatial-planning documents, the Heat Supply Scheme of Zainsk, regional environmental analytical materials, and data on stationary emission sources. The comparison is carried out using a unified framework that includes the number of stationary emission sources, the volume and sectoral profile of emissions, dominant sources of pollution, infrastructure conditions, spatial-planning constraints, and potential instruments of municipal implementation. Available environmental materials indicate that Mendeleevsk has about 649 stationary emission sources and approximately 3.709 thousand tons of stationary-source emissions, with the fuel and chemical sectors forming the main industrial contribution; Zainsk has about 1 071 stationary sources, including 1 061 within the town, and about 11.741 thousand tons of stationary-source emissions, including 11.728 thousand tons within the town. It is established that Mendeleevsk represents a type of small town with a chemical-industrial core, where priority measures include technological decarbonization, modernization of gas-cleaning systems, stricter environmental monitoring, and spatial regulation of zones adjacent to industrial sites. Zainsk is characterized by a combination of power generation, heat supply, transport flows, and agro-processing, which requires modernization of generating capacities, optimization of district heating, energy-efficiency measures, and circular solutions based on industrial symbiosis. The paper concludes that low-emission planning in small industrial towns should be differentiated by territorial type and embedded in municipal strategic, spatial-planning, infrastructure, and monitoring systems.